Modification of the Renal Angina Index for identifying the need for renal replacement therapy in critically ill pediatric patients - Stenson, Erin K; Brinton, John T; Beil, Liz; Soranno, Danielle E; Gist, Katja M (Journal of Clinical Nephrology, 2020)
Severe Acute Kidney Injury (AKI) is a common, serious problem affecting critically ill children that lacks effective treatment options. Currently, there are no treatment options for AKI other than supportive care. Continuous renal replacement therapy (CRRT) is employed to reduce Fluid Overload (FO) burden and treat metabolic disturbances in AKI. Identifying patients upon admission who may require CRRT has potential clinical care implications. The aim of this study was to determine if the RAI had diagnostic capabilities to identify patients who would require CRRT. The analytic cohort consisted of patients who required CRRT and illness severity score matched controls who did not require CRRT at a single center. Patients who required CRRT had higher mortality rates, length of stay, and use of ventilatory and inotropic support. Sensitivity, specificity and area under the receiver operating characteristic curve (AUC) assessed and compared the discriminatory accuracy of three scores: 1) the renal angina index (RAI), 2) serum-creatinine (sCr) based AKI on day 0 and 3) modified RAI created with an additional RAI injury tranche that corresponded to severe stage 3 AKI sCr elevation. Compared to Day0AKI (AUC 0.78, 0.70-0.87; sensitivity 0.63, 0.45-0.79; specificity 0.93, 0.870.97) and RAI (AUC 0.76, 0.69-0.82; sensitivity 0.94, 0.81-0.99; specificity 0.57, 0.47-0.66), the modified RAI had the highest AUC (0.79; 0.72-0.85) with a high sensitivity (0.91; 0.77-0.98) and moderate specificity (0.65; 0.56-0.75) for prediction of CRRT requirements. As a more accurate tool for discriminating patients in need of CRRT, a modified RAI has numerous potential implications. Identifying patients who ultimately require CRRT at an earlier timepoint may influence timing of CRRT initiation in an attempt to avoid further FO, or may influence nephrotoxin administration. The diagnostic capabilities of the modified RAI may be refined by the addition of urinary biomarkers. These findings should be validated in a larger cohort.